2020
DOI: 10.1016/j.biombioe.2020.105710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leucaena biochar addition on crop productivity in degraded tropical soils

Abstract: Biochar has the potential to increase crop yields on degraded, tropical soils. It can be readily produced in rural community settings using low-cost technology and is most economically feasible if produced from local biomass or waste residues. Biochar was produced from Leucaena biomass using low-cost pyrolysis and sequential pot experiments were then conducted in Malaysia on three degraded soils. We first evaluated the effect of Leucaena biochar on yields of Amaranthus, a leafy vegetable crop and measured chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…The increased pH at kiln sites could be attributed to the high pH of biochar used (Li et al., 2021; Mulualem et al., 2021; Zhu et al., 2014) and the addition of ashes formed from burnt materials during the carbonization process which release basic cations in oxide or carbonate forms (Domingues et al., 2017; Glaser et al., 2002; Goulding, 2016). A. decurrens wood biochar had a pH of 9.84 (Table 1) exhibiting its alkalinity nature which reflects the positive effect of its application to ameliorate soil acidity by raising the pH of acidic soils (Elias et al., 2020; Zhu et al., 2014). The accumulation of basic cations released from ashes at kiln sites (Gómez‐Luna et al., 2009; Thomaz, 2017) will alter soil pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased pH at kiln sites could be attributed to the high pH of biochar used (Li et al., 2021; Mulualem et al., 2021; Zhu et al., 2014) and the addition of ashes formed from burnt materials during the carbonization process which release basic cations in oxide or carbonate forms (Domingues et al., 2017; Glaser et al., 2002; Goulding, 2016). A. decurrens wood biochar had a pH of 9.84 (Table 1) exhibiting its alkalinity nature which reflects the positive effect of its application to ameliorate soil acidity by raising the pH of acidic soils (Elias et al., 2020; Zhu et al., 2014). The accumulation of basic cations released from ashes at kiln sites (Gómez‐Luna et al., 2009; Thomaz, 2017) will alter soil pH.…”
Section: Discussionmentioning
confidence: 99%
“…Biomass and grain yields of wheat in CSH under the pot experiment were increased by over 170% compared with RSF. The yield increase in CSH is greater compared with the yield increase by 17%–54% following biochar addition at 15 and 30 Mg ha −1 with fertilizer (Elias et al., 2020), or meta‐analysis for biochar combined with inorganic fertilizer that can increase crop yield by 15% (Ye et al., 2020). Maintaining higher wheat productivity in charcoal‐amended soil even with a reduced inorganic fertilizer application suggests that inclusion of charcoal production in the cropping system may reduce the need for inorganic fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar has been proposed as a potential soil amendment to improve soil quality and increase aboveground biomass (Banik et al, 2021; Elias et al, 2020) and dry matter content (Yakubu et al, 2020) particularly on degraded or highly weathered tropical soils. In the current study, pig manure digestate‐derived biochar treatments (M1B1, M2B1 and M3B1) significantly enhanced aboveground biomass and dry matter compared to non‐biochar treatments (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Even though growing biomass on low-quality land can improve the soil quality, yields from such soils can be low. Elias et al [9] showed in their SI article that one way of addressing this is through the application of biochar. As an agricultural soil amendment and conditioner, biochar can improve soil fertility and biomass yields, particularly on acidic and highly weathered and degraded soils across the humid tropics [9].…”
Section: Environmental Impactsmentioning
confidence: 99%